Religion, Gender and Medicine: The Nursing and Midwifery Practice of an English Woman Missionary in Yunnan and its Implications, 1933-1939 - LI, Minghui (Journal of Research for Christianity in China (JRCC), 2023)
Women medical missionaries’ work in China in the modern period had not only impacted on the way Chinese women consulted medical advice profoundly, but also promoted the spread of Western Gynecological and Obstetrical knowledge as well as the modern medical education for women. This article, however, attempts to explore the significance and problems of women medical missionaries’ work in terms of religion, gender and medicine through focusing on the story of the English missionary Mildred Button. Mildred Button came to Zhaotong, Yunnan as a nurse and midwife in 1932 but resigned from her work only six years later due to health and family issues. Her post in China was changed several times during the course, and it seems that she did not have a so-called “successful” missionary career. However, she kept writing diary when she was in China and carefully registered each of her midwifery case, thus leaving valuable records about her work. Based on her records, this article tries to analyze how her faith in medical missionary formed, how she performed professional duties within a given medical hierarchy, and how her midwifery work was conducted in and restrained by local health resources as well as societal and cultural norms. Through these analyses, this article hopes to further respond to some remained research inquiries regarding the medical missionary and nursing/midwifery in modern China.
Keywords: Medical Missionary, Nursing and Midwifery, Professional Remit of Doctor and Nurse, Yunnan